Administration and management strategies of archery athletes for excellence - Rodma, G.; Khaowanna, Y.; Hemara, C. (Journal of Positive Psychology and Wellbeing, 2022)
Designing the quantitative and qualitative research method were to analyze and synthesize the database of the Thai archers to the draft, an administration and management strategies of archery athletes for excellence model were created. Creating the Ethnographic Delphi Futures Research (EDFR) with Delphi methodology to the Thailand National Sports University sample target group, consisting of 28 university administrators, 28 archery trainers, 17 executive administrators of the higher education institutions, and 113 archery athletes were administered. The factors that make athletes successful, covering nine issues, consisting of the trainers, facilities, sports science, creating the competitive experience, athletes, selection of athletes, administration and management, support and encouragement, and training and practicing assessed to the 45-item Administration and Management of Archery for Excellence Questionnaire (AMAEQ). The AMAEQ was valid and reliable for each item with the Factor Loading Analysis, and a-reliability on nine scales in three rounds by the archery professional experts` perceptions was correlated. The results indicate problems in Training and Practicing, Facility, Trainer, and Administration and Management Strategy scales that are improved to determine the direction of the strategy to draft the administration and management model. Comparisons between the grand means between the 1st and 2nd rounds are significant differences. Statistically, effective all on nine scales between the 1st and the 3rd rounds and are differentiated (p<.001). Regarding the 2nd and the 3rd rounds, four of the nine scales are different, significant at .05 levels with t-test analysis. The effect size (eta 2) between the two variables` relationships at the databases' small and medium effect sizes. However, the problems that should be improved include the limited number of archery trainers and archery clubs still lacking standard sports equipment for expensive training In order to improve and solve the aforementioned problems, to draft a strategy to develop archery athletes of Thailand towards excellence to participate in archery competitions at the Olympic level with Delphi methodology and has been improved to be more flexible and appropriate for this research study under the strategy of 20 years after.